МНЕМОНИЧКИ ИМПЛИКАЦИИ НА ТОПОСОТ (Филолошки студии, 2019)
This text is an attempt to systematize theoretical and mnemonic implications of the topos figure of memory. Theoretical frame of the text refers to some conceptions of Y.M. Lotman, R. Lachmann, I. Smirnov and D.O. Tolic. The subject of analysis are literary texts of three Macedonian authors: a cycle of poems about Marko Krale by Blaže Koneski, the novel Marko Krale by Slobodan Mickovik and the play Bolen Dojčin by Georgi Stalev. The purpose of their interpretation is to confirm the validity and functionality of the topos figure of memory in interpretative and theoretical sense.
Keywords: topos, figure of memory, memory, literature, intertextuality, metatextuality, literary tradition as a prototext